Evaluation of Robotic-Assisted Laparoscopic and Open Pyeloplasty in Children: Single-Surgeon Experience - Murthy, P (Ann R Coll Surg Engl, 2015)
INTRODUCTION: Robotic-assisted laparoscopic pyeloplasty (RALP), the most commonly undertaken paediatric robotic urologic surgery, has not been compared against open pyeloplasty (OPN) by a single surgeon. Here, we describe our experience and outcomes. METHODS: Children undergoing RALP or OPN from 2007 to 2013 were reviewed. Clinical success was defined as resolution of presenting symptoms and improved/stable hydronephrosis on ultrasound. RESULTS: RALP and OPN cohorts comprised 52 and 40 patients, respectively. RALP patients were significantly older (6.8 vs 1.2 years, p<0.01) and heavier (28.4 vs 8.4 kg, p<0.01). Operative times for RALP were longer (203.3 vs 135.0 min, p<0.01), but decreased significantly with increasing experience (r(2)=0.42, p<0.01). Seven type-IIIb Clavien–Dindo complications occurred in RALP patients compared with two in OPN cases. There were no differences in postoperative narcotic administration (p=0.92) or duration of stay in hospital (DOSH) (p=0.93). A total of 11/40 (28%) OPN patients required epidural analgesia but none were placed in the RALP cohort. A total of 49/52 (94%) RALP patients and 40/40 OPN cases had successful outcomes. Three RALP patients required revision RALP. CONCLUSIONS: These data show that outcomes for RALP and OPN were comparable. An initial learning curve with RALP is to be expected, but operative times for RALP approached those for OPN. Previously reported benefits of RALP (reduced analgesic requirements, DOSH) were not observed. This difference may have been due to comparison of a heterogeneous cohort. Close evaluation of complications allowed for improved placement of stents in RALP.